MORPHOLOGICAL PROFICIENCY OF EFL STUDENTS IN NORMALIZING VERBS WITH SUFFIXES - Islamiati, Dini; Bochari, Siska; Mertosono, Sudarkam R.; Lebagi, Desrin (Jurusan Sastra Indonesia, 2024)
The purpose of this research was to determine which suffix students most frequently used and the factor of difficulty they encountered when converting verbs to nouns using nominal suffixes. Tests and questionnaires were used in the study's quantitative descriptive design to gather information from fifth-semester English education study program students. The findings indicate that students had no problems and that the most common suffix used was -ing.